SOSIALISASI MPASI SEBAGAI BENTUK PENCEGAHAN STUNTING - Habib, Adeztina Irfani; Silviani, Marsya Arzeta (COMMENT: Journal of Community Empowerment, 2023)
Stunting refers to toddlers whose height or length is below the average compared to standards. Insufficient nutritional intake is one of the causes of stunting. This issue can be addressed by providing Complementary Feeding (CF). CF is given to toddlers alongside breastfeeding to enhance their nutrition. The Kukerta Team from the University of Riau organized a socialization program on CF and stunting with the aim of reducing stunting rates and enhancing the understanding of Health Cadres, expectant mothers, and mothers with young children regarding these issues. The implementation of this program began with participation in Posyandu activities, followed by the core program of CF and stunting awareness. The activities proceeded smoothly. Through the evaluation results, it is hoped that in the future, there will be more in-depth CF and stunting awareness programs.